Going APE over ref-1 - Evans, Angela R.; Limp-Foster, Melissa; Kelley, Mark R. (Mutation research, 2000)
The DNA base excision repair (BER) pathway is responsible for the repair of cellular alkylation and oxidative DNA damage. A crucial and the second step in the BER pathway involves the cleavage of baseless sites in DNA by an AP endonuclease. The major AP endonuclease in mammalian cells is Ape1/ref-1. Ape1/ref-1 is a multifunctional protein that is not only responsible for repair of AP sites, but also functions as a reduction-oxidation (redox) factor maintaining transcription factors in an active reduced state. Ape1/ref-1 has been shown to stimulate the DNA binding activity of numerous transcription factors that are involved in cancer promotion and progression such as Fos, Jun, NF(B, PAX, HIF-1(, HLF and p53. Ape1/ref-1 has also been implicated in the activation of bioreductive drugs which require reduction in order to be active and has been shown to interact with a subunit of the Ku antigen to act as a negative regulator of the parathyroid hormone promoter, as well as part of the HREBP transcription factor complex. Ape1/ref-1 levels have been found to be elevated in a number of cancers such as ovarian, cervical, prostate, rhabdomyosarcomas and germ cell tumors and correlated with the radiosensitivity of cervical cancers. In this review, we have attempted to try and assimilated as much data concerning Ape1/ref-1 and incorporate the rapidly growing information on Ape1/ref-1 in a wide variety of functions and systems.